2011
DOI: 10.1007/s12272-011-0317-7
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B reverses the epithelial-to-mesenchymal transition of HK-2 cells that is induced by transforming growth factor-β

Abstract: Salvianolic acid B (Sal B) is the most abundant bioactive molecule from Radix Salviae Miltiorrhizae, and has recently been used for treating renal fibrosis in traditional Chinese medicine. Here we investigated the ability reversal of Sal B to reverse the transdifferentiation of human kidney proximal tubular epithelial cells that was induced by transforming growth factor-beta 1 (TGF-β1). The effects of Sal B on HK-2 cell morphology were observed by phase contrast microscopy, while alpha smooth muscle actin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…The inhibition of E-CA downregulation and α -SMA upregulation seen in the current studies was maximal with 250  μ g/mL concentration of TXL. This pharmacological mechanism of TXL inhibiting EMT is absolutely in accordance with previous studies; Hung et al demonstrated that counteract TGF- β 1 and its downstream signal transducers, like smad3 and smad7, may be an effective therapy in inhibiting EMT [24, 41]. The present study also showed that TXL is able to negatively modulate TGF- β 1 signaling at several levels.…”
Section: Discussionsupporting
confidence: 92%
“…The inhibition of E-CA downregulation and α -SMA upregulation seen in the current studies was maximal with 250  μ g/mL concentration of TXL. This pharmacological mechanism of TXL inhibiting EMT is absolutely in accordance with previous studies; Hung et al demonstrated that counteract TGF- β 1 and its downstream signal transducers, like smad3 and smad7, may be an effective therapy in inhibiting EMT [24, 41]. The present study also showed that TXL is able to negatively modulate TGF- β 1 signaling at several levels.…”
Section: Discussionsupporting
confidence: 92%
“…Modern pharmacological studies have demonstrated that each single drug in Kangxianling decoction could be useful in chronic kidney disease. For example, radix salviae miltiorrhiza was proved to be able to reverse the transdifferentiation of human renal proximal tubular epithelial cells induced by TGF- β 1, thus delaying the procession of renal fibrosis in injured kidneys [18]. Rhubarb could alleviate tubulointerstitial fibrosis by inhibiting TGF- β /Smad pathway in chronic kidney disease [19].…”
Section: Discussionmentioning
confidence: 99%
“…S. miltiorrhiza can promote the circulation system in wounded tissue (Figure 7). It may improve the burn wound healing process by removing necrotic cells, attenuating the inflammatory response and apoptosis [12,21], reducing oxidative stress [12], and possibly facilitate the repair of tubular epithelia structures [23]. …”
Section: Discussionmentioning
confidence: 99%